2014
DOI: 10.4081/aiua.2014.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Management of bladder stones associated with foreign bodies following incontinence and contraception surgery

Abstract: In conclusion endoscopic lithotripsy is a safe and effective approach to manage bladder stone associated with mid-urethral synthetic slings and intrauterine devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Endoscopic lithotripsy combined with electro-resection is a successful option for such bladder stones (2,5). In the presented case the stone was crushed with the pneumatic lithotripter and the mesh resected with electrocautery.…”
Section: Resultsmentioning
confidence: 92%
“…Endoscopic lithotripsy combined with electro-resection is a successful option for such bladder stones (2,5). In the presented case the stone was crushed with the pneumatic lithotripter and the mesh resected with electrocautery.…”
Section: Resultsmentioning
confidence: 92%
“…It was found that the experimental group had shorter the surgery time and hospital stay, and a higher calculus removal rate. Studies have shown that, holmium laser lithotripsy demonstrates good safety and has been extensively used (22).…”
Section: Discussionmentioning
confidence: 99%